Mel brooks - make a noise [videorecording (DVD)]. - Leachman, Cloris; Broderick, Matthew, 1962-; Lane, Nathan, 1956-; Brooks, Mel, 1926-; Rivers, Joan; Reiner, Carl, 1922-2020- (Shout Factory, 2013)
Mel Brooks has energetically avoided a documentary profile from being made, until now. He has agreed to throw himself into a new documentary about his storied career, giving American Masters exclusive interviews and complete access to his film archives.